DECISION SUPPORT SYSTEM DESIGN MODEL FOR PRODUCTION RESULT EVALUATION IN CENTRAL JAVA AUTOMOTIVE COMPANY - BILHAN GAMALIEL HARTANTO; GALI PRIBADI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Effective decision making requires the implementation of a Decision Support System (DSS) that combines data, automated simulation models, and interactive visualization. This DSS plays a role in improving the efficiency of machine scheduling, identifying production lines that require overtime, and designing action plans for lines that fail to achieve production targets. The use of Macro VB Excel facilitates the acceleration of data collection and problem analysis using fishbone diagrams and FMEA, which reduces analysis time by 2.7 hours and requires additional overtime of 6.1 shifts to achieve the production target of 19,277 pcs. In the production meeting, four action plans were proposed including the creation of Standard Operating Procedures to reduce machine adjustments, routine overtime assignments, different operations for materials from certain suppliers, and standardization of parameters for each production process.